Effectiveness of Antidiarrheal Unripe Wooden Banana (Musa paradisiaca L.) in Male Balb-C/Mice Induced with Escherichia coli - Ningsih, Arista Wahyu; Rochmanti, Maftuchah; Basori, Achmad (Folia Medica Indonesiana, 2020)
The survey results in Indonesia in 2017 showed that the diarrhea morbidity rate for all age groups was 6.897.463. In Indonesia, unripe wooden banana has been used empirically as an antidiarrheal by the people in Senduro village, Lumajang, East Java. The study aimed to prove the antidiarrheal effect of ethanol extract of unripe wooden banana (Musa paradisiaca L) in male Balb-C/mice induced by Escherichia coli bacteria.This study was a laboratory experimental study with post-test only control group design that used 40 micedivided into 8 groups, namely 1group without treatment (normal mice) and 7 groups induced by Escherichia coli(1negative controlgroup given CMC-Na, 3 groups positive controls were given Loperamid HCL 0,5 mg/kgBB, 1 mg/kgBB and 2 mg/kgBB and 3 treatment groups were given extracts 100 mg/kgBB, 200 mg/kgBB and 400 mg/kgBB). Observation of animals in this study was carried out for 4 hours. Data were analyzed of frequency of diarrhea, fecal weight and fecal consistency used Kruskal Wallis and the results showed significant differences between treatment groups (p <0.05). From the results of the Mann-Whitney test, the ethanol extract of unripe wooden banana with a dose of 100 mg/kgBB was notsignificantly different (p> 0.05) with the control group of Loperamid HCL dose of 0.5 mg/kgBB. Unripe wooden banana had been shown to have antidiarrheal activity at an extract dose of 100 mg/kg BB in terms of the parameters of fecal consistency, frequency of diarrhea, and fecal weight. The results showed that the higher the dose, the better antidiarrheal activity